Distribuição espacial e temporal dos acidentes causados por escorpião no município de Natal, estado do Rio Grande do Norte (2007-2018) - Araújo, Kaliany Adja Medeiros de (2025)
Scorpion venomous animal`s accident is considered a public health problem in tropical and subtropical countries around the world. The high incidence of these cases reveals the need of studies to determine the diversity of signs and symptoms of this spatial distribution, especially in the city of Natal-RN, a hot and humid region with many cases of scorpion stings. The objective of this study was to investigate the spatial and temporal distribution, as well as the clinical and environmental aspects involved in scorpion sting accidents in the city of Natal, Rio Grande do Norte state. For this purpose, data were obtained from the database of notifiable diseases in Health Secretary from Rio Grande do Norte State (SESAP-RN) and the Information System for Notifiable Diseases (SINAN), between the years 2007 and 2018. In the region, 31,368 cases of people affected by scorpions were registered, with a higher concentration in areas of greater urbanization and lower Human Development Index (HDI), sewage disposal and garbage collection rates. The accidents occurred in predominantly hot and humid regions, mainly affecting women of economically active ages. Furthermore, it was observed that the first three hours after the sting are crucial for the prognosis of the cases. The clinical symptoms mostly present pain, followed by edema and numbness. Considering that this is a neglected problem, and taking into account the location of the municipality, it is possible to see how environmental issues influence the spatial distribution and maintenance of an ecosystem favorable to scorpionism. Based on the data collected on the characterization of spatial distribution and its risks, this research can contribute significantly to mitigating strategies for preventing new accidents.